The relationship between early adulthood obesity and sarcopenic obesity among middle-aged and older adults in the United States - Cheng, Gang; Zhou, Ying; Wang, Yan; Wang, Chunguang; Xu, Jianghong (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore the relationship between early adulthood obesity and sarcopenic obesity (SO) among middle-aged and older adults in the United States.MethodsThis retrospective study was conducted involving adults aged 50–69 years in the United States. Data were extracted from the National Health and Nutrition Examination Survey (NHANES) during the periods 1999–2006 and 2011–2018. Height and weight at the age of 25 years were measured. Body mass index (BMI) at the age of 25 years (BMI25) was calculated. Healthy weight, overweight, and obesity at the age of 25 years (healthy weight25, overweight25, and obesity25) were defined as BMI25 18.5 to less than 25 kg/m2, 25 to less than 30 kg/m2, and 30 kg/m2 or greater, respectively. SO was determined by dividing appendicular skeletal muscle mass by weight (ASM/Wt) and percentage of fat mass [FM (%)].ResultsThe prevalence of SO was 5.4, 8.5, and 16.5% in healthy weight25, overweight25, and obesity25 groups, respectively. After adjusting for confounding factors, the prevalence of SO in the overweight25 group and the obesity25 group was 1.161 times (95%CI: 0.898–1.500, p = 0.254) and 2.286 times (95%CI: 1.651–3.165, p < 0.001) higher, respectively, compared to the healthy weight25 group.ConclusionThis study demonstrates that obesity in early adulthood is closely associated with an increased risk of sarcopenic obesity among middle-aged and older adults.